(untitled) (The Conference Hub, 2025)
Thyroid cancer is one of the urgent problems in oncological practice, and its various histological forms are characterized by different clinical course and prognosis. Molecular genetic markers - in particular, such indicators as Ki-67, p53, CD34 - are of great importance in determining individual treatment tactics and prognostic assessment in patients.